Development of Interactive Learning Media on Science Learning Outcomes of Junior High School Students in Papua - Askar; Asrowi; Yamtinah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2026)
Education in Papua faces significant challenges in the form of limited infrastructure, access to education, and conventional learning methods that have an impact on low motivation and student learning outcomes, especially in science subjects. This research aims to develop valid and feasible interactive learning media for science for students in Papua, as well as analyze its influence on student learning outcomes. The research method uses the Research and Development (R&D) approach with the ADDIE model which includes the Analysis, Design, Development, Implementation, and Evaluation stages. Validation was carried out by media and material experts, as well as trials on 60 grade IX students at SMP Negeri 2 Agats and SMP YPPK Agats which were divided into experimental and control groups. The results of expert validation showed that the media obtained an average score of 4.3 out of a scale of 5, indicating a very high level of eligibility. The results of the pre-test and post-test showed that the experimental group experienced an increase in learning outcomes by 15 points (from 65 to 80), while the control group only increased by 4 points (from 66 to 70). The t-independent test yielded a calculated t-value of 4.55 > t table 2.003 with a p-value of 0.003 (p<0.05), confirming a significant difference between the two groups. This study concludes that interactive learning media is effective in improving the science learning outcomes of students in Papua and is recommended to be widely implemented with the support of technology infrastructure and continuous teacher training.